USAGE AND MEANING DIFFERENCES OF PAST TENSE FORMS IN JAPANESE - Komilova Rohilaxon Rustamjon kizi (Bright Mind Publishing, 2025)
Our need for language in our daily lives is significantly high. In the process of using this language, we compose sentences using various expressions and grammars so that the idea we want to convey is easy to understand for others. This scientific article discusses the use and differences in meanings of past tense forms in Japanese.
Keywords: Verb, tense, past tense, grammar, context, learner, vehicle, agglutinative.